Do we really care about artificial intelligence? A review on social transformations and ethical challenges of AI for the 21st century - Guerreiro, J. (Managerial challenges and social impacts of virtual and augmented reality, 2020)
Although Artificial Intelligence (AI) is based on research from the 20th century, computation and new algorithms have only recently allowed AI to gain momentum and practical applications in society. Examples of such uses include self-driving cars and autonomous robots that are changing society and how we interact. Despite these advances, the discussion about the social transformations and ethical implications of this new reality remains scarce. This chapter reviews the current stance of ethical and social transformation discussions on AI and presents a framework for future developments. The main contributions of the chapter allow researchers to understand the major gaps in research that may be explored further in this topic and allow practitioners to gain a better picture of how AI may change society in the near future and how society should prepare for those changes.